-18=3(z+-10)

Simple and best practice solution for -18=3(z+-10) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -18=3(z+-10) equation:



-18=3(z+-10)
We move all terms to the left:
-18-(3(z+-10))=0
We add all the numbers together, and all the variables
-(3(z-10))-18=0
We calculate terms in parentheses: -(3(z-10)), so:
3(z-10)
We multiply parentheses
3z-30
Back to the equation:
-(3z-30)
We get rid of parentheses
-3z+30-18=0
We add all the numbers together, and all the variables
-3z+12=0
We move all terms containing z to the left, all other terms to the right
-3z=-12
z=-12/-3
z=+4

See similar equations:

| 2v+9-6=-19 | | 150m-75m+42975=46125-150m | | |x+8|=14 | | 4x*2.5=2x-3 | | 10(w-87)=100 | | 37+6p=(p+6)+1 | | 4(x-7)=0.3(x | | 96=6(y-78) | | a/5+3=5 | | x^2=25/36= | | 5s-22=78 | | 0=m+6m | | 8(b+2)=72 | | 9z-6=11z-7 | | k/2+13=16 | | 6-1=40m | | x/1.5+4.3=-8 | | 5b+11=56+4b | | -25x^2+35x=0 | | 0.40x-0.20(40+x)=0.10(40) | | 1/2t^2=9 | | 5=k+6/6 | | 2x+58=84 | | 6+8a=3 | | -15=-6n+n | | c+32/9=5 | | c/7+8=11 | | v/5+21=27 | | 11x+2=15x-4 | | 6=4n-14 | | -8w+-22=18 | | 4m-27=57 |

Equations solver categories